A blended e-health intervention for improving functional capacity in elderly patients on haemodialysis: A feasibility study - Zemp, Damiano D.; Baschung Pfister, Pierrette; Knols, Ruud H.; Quadri, Pierluigi; Bianchi, Giorgia; Giunzioni, Davide; Lavorato, Soraya; Giannini, Olivier; de Bruin, Eling D. (Frontiers in Digital Health, 2022)
Introduction: Physical exercise showed to be beneficial for the elderly population on haemodialysis (HD) that is known to be frail. However, there are several obstacles, such as transportation difficulties, lack of time, fatigue and comorbidities, which hinder the regular practice of exercise. E-health in this regard has many potential advantages and could be useful for motivating HD patients to increase their level of physical activity. The aim of this study is to evaluate the feasibility of a blended e-health intervention for elderly HD patients who exercise at home individually, under remote supervision of a physiotherapist. Material and methods: Patients over 60 with sufficient cognitive and motoric resources to perform a simple physical test battery and to use a tablet-computer were recruited from four HD outpatient facilities. Following baseline assessment at home, the participants were visited by a physiotherapist (PT), who set an individual exercise programme and explained how to use the web-based interface. During the 12 weeks of training, the PTs remotely supervised the patients’ progress. At 12 weeks follow-up a second assessment battery was performed. Results: Twenty-two patients were recruited for participation in the study. Seven patients dropped out of the blended programme and 15 patients concluded the programme. The average training frequency of the 15 participants concluding the study was 1.5 times a week [range 0.2 – 5.8]. The duration of a training session was between 20 and 40 minutes. The usability of the system was deemed positive. Regarding the efficacy of the intervention, no significant improvement of any measured parameter was found, and effect sizes were small to medium. Conclusion: A blended e-health intervention supported by a web-based application for exercising at home under remote supervision of a PT is feasible in a HD population including older patients. However, before planning a randomized controlled trial, strategies to increase the recruitment rate and the adherence to such a blended intervention should be further developed, e.g., to improve the recruitment procedures and lower the expectable drop-out rate. Furthermore, the dosage of the blended programme should be adapted to the patients’ physical performance levels in future trials.